A development of a dielectric composite substrate based on barium titanate-epoxy resin for a 5 GHZ microstrip antenna - Nur Sofia Idayu, Didik Aprianto; Nurul Izzah Izzaty, Mohd Nadzri; Nurfarhana, Mustafa; Muhammad Hazarul Azmeer, Ab Malek; Ahmad Afif, Mohd Faudzi; Mohamad Shaiful, Abdul Karim (IEICES/Kyushu University, 2025)
This study focuses on investigating the potential of a barium titanate-epoxy resin composite as a substrate for a microstrip patch antenna at 5 GHz. Barium titanate exhibits excellent dielectric properties, and epoxy resin, known for its robust thermosetting polymer, was combined to create one composite material. The permittivity and loss tangent of the composite material were measured using the waveguide technique over a frequency range of 4 GHz to 6 GHz. To determine the compatibility of the composite substrate for a microstrip patch antenna at 5 GHz, the values of return loss and Voltage Standing Wave Ratio (VSWR) were analyzed. The barium titanate-epoxy resin sample resulted in a high permittivity value of 7.0208 and a low loss tangent of 0.0238, which can contribute to a compact antenna design with high efficiency. The fabricated antenna results in a return loss of -42.52 dB and VSWR of 1.137 at 5 GHz, showing its effectiveness for wireless communication applications.